Goth : a history - Tolhurst, Laurence (Hachette Books, Hachette Book Group, 2023)
"GOTH is an entertaining and engaging historical memoir of the genre of Goth music and culture, exploring creative giants like The Cure, Siouxsie and the Banshees, Bauhaus, Joy Division, and many more great bands that offered a place of refuge for the misfits of the 80s and ever since. Written by Lol Tolhurst, co-founder of The Cure, this book offers a fascinating deep dive into the movers and shakers of goth with stories and anecdotes from Tolhurst's personal memories as well as the musicians, magicians, and artists, who made it all happen--the people, places, and events that made goth an inevitable and enduring movement. Starting with the Origins of Goth, Tolhurst explores early art and literature that inspired the genre and looks into the work of T.S Eliot, Edgar Allan Poe, Sylvia Plath, Albert Camus and more. He also outlines the path of Gothic Forebears and shows how many musicians played in punk bands before transitioning into goth endeavors. Next, he introduces readers to the "Architects of Darkness"--Bauhaus, Siouxsie and the Banshees, Joy Division and The Cure--the godfathers of goth who established the genre's roots. Following these early bands, Tolhurst discusses a group he calls the "Spiritual Alchemists", consisting of bands like Depeche Mode, Cocteau Twins and more, who helped the darkness expand into the culture. He also tracks the expansion of the genre overseas, from England to New York, Los Angeles, and beyond. Gothic fashion was an important part of the movement as well, and Tolhurst discusses the clothing that accompanied and complemented the music. Finally, Tolhurst examines the legacy of goth music, and shows how its influence can still be seen to this day across music, film, TV, visual arts, social media, and so much more finally concluding "Why Goth matters!""--